ONLINE MARKETING FOR THE INDONESIAN TOURISM INDUSTRY IN COVID-19 - SUNDAY ADE SITORUS; TRI MELDA MEI LIANA; ANITA TRESIA SAMOSIR; SUNDAY ADE SITORUS (JURNAL ILMIAH SIMANTEK, 2022)
Indonesian commerce firms are reporting a high rate of online sales as consumers engage in social media amidst the Covid-19 outbreak, with the government looking at a thriving sector as one way to address the tax cuts caused by the global recession. Compared with neighbouring countries Malaysia and Singapore, the Indonesian government has been reluctant to adopt strict segregation procedures due to fears of economic and social impact. The closure was announced in an effort to curb the spread of coronavirus, with Indonesia reporting 5136 cases and 469 deaths. The most populous capital is considered to be the epicentre of an outbreak in Indonesia, accounting for 50% of all cases. Charges Prior to the announcement of the partial closure, many large companies in Jakarta were already implementing local employment policies following requests from national and local governments. In addition, some shopping malls, retailers, and restaurants have taken joint decisions to reduce business hours, switch to online activity, or stop trading altogether. Since the first half of 2020, the Indonesian tourism industry has lost about $ 85 billion in tourism revenue. Apart from this, the hotel and restaurant industry estimates Indonesia's nearly 70 trillion losses. The COVID-19 epidemic has had a devastating effect on the tourism industry, as international travel has been suspended to curb the spread of the virus.